2022
DOI: 10.3389/fpls.2022.854127
|View full text |Cite
|
Sign up to set email alerts
|

Genome Dominance in Allium Hybrids (A. cepa × A. roylei)

Abstract: Genome dominance is a phenomenon in wide hybrids when one of the parental genomes becomes “dominant,” while the other genome turns to be “submissive.” This dominance may express itself in several ways including homoeologous gene expression bias and modified epigenetic regulation. Moreover, some wide hybrids display unequal retention of parental chromosomes in successive generations. This may hamper employment of wide hybridization in practical breeding due to the potential elimination of introgressed segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Similar results were observed in Allium cepa L. × Allium roylei Stearn. hybrids (Kopecký et al ., 2022). Unfortunately, direct observation of chromosome behavior in female meiosis is not feasible; hence, sample sizes are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed in Allium cepa L. × Allium roylei Stearn. hybrids (Kopecký et al ., 2022). Unfortunately, direct observation of chromosome behavior in female meiosis is not feasible; hence, sample sizes are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In interspecific hybrids, the frequency of such attachments and the ability to be included in the newly formed nuclei may differ between univalents of different parental origin. Indeed, some hybrids show higher elimination rate of chromosomes from the submissive genome (Kopecký et al ., 2022). An extreme case is the instant elimination of one parental chromosome set after hybridization of Hordeum vulgare L. with Hordeum bulbosum L. during first embryo mitoses (Sanei et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Lolium × Festuca interspecific hybrids, which show preferential loss of Festuca chromosomes, Majka et al ( 2023 ) were able to attribute this preferential chromosome loss effect to subgenome-specific ( Lolium- only) expression of kinetochore proteins controlling attachment of univalent chromosomes to microtubules, such that Festuca chromosomes were improperly attached and subsequently often lost as micronuclei following meiosis. Similar bias towards inheritance of Allium roylei over A. cepa chromosomes in A. cepa × A. roylei hybrids was attributed to female meiotic drive (Kopecký et al 2022 ). Similar meiotic mechanisms may be operating in our BBAC S 1 hybrids, but further investigation would be required to confirm or refute this hypothesis.…”
Section: Discussionmentioning
confidence: 66%
“…It enables a shift in the genome composition in hybrid progeny. In Allium cepa × A. roylei hybrids, the A. roylei genome appears to predominate: the percentage of roylei alleles in the F 2 population was on average 56% vs. 44% of cepa alleles and the parental chromosome constitution shifted from 8cepa + 8roylei in F 1 gen-https://doi.org/10.17221/19/2022-CJGPB eration to 6.7cepa + 9.3roylei in F 2 generation (van Heusden et al 2000;Kopecký et al 2022). Earlier studies observed chromosomal dominance in all cultivars selected from Lolium multiflorum × Festuca pratensis hybrids.…”
Section: Homoeologous Chromosome Pairing Opens a Way For Genome Domin...mentioning
confidence: 99%
“…This creates an opportunity to direct certain chromosomes preferentially to the egg cell and hence, to the next generation, and eliminates their counterparts. Recent research indicates that the female meiotic drive is the most probable explanation of the Lolium-and A. roylei-genome dominance (Kopecký et al 2022). Female meiotic drive underlying subsequent substitution of one parental genome by the other has been only rarely reported in plant hybrids (Fishman & Saunders 2008).…”
Section: Homoeologous Chromosome Pairing Opens a Way For Genome Domin...mentioning
confidence: 99%